INVESTIGATING THE EFFECT OF ECONOMIC DETERMINANTS ON STOCK MARKET RETURNS: AN INTROSPECTION (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
Similar to everything else in life, higher the  risk, larger is the return. Distinct from other  investment options, stock market investments are  riskier but the rewards are also equally handsome  and attractive. The foremost reason behind such  risk is market volatility or fluctuations. By nature  the stock market is exceptionally erratic. Many  times for unknown reasons the shares prices can  go up or come down randomly. Owing to this  impulsiveness, investments in such markets are  deemed to be risky proposition. Nevertheless,  if time is invested in properly studying the  market and its randomness in detail, rewards  can be reaped substantially. The foremost step  towards this is to comprehend the reasons  behind stock price movements. Using step-wise  regression this paper examines the impact of  few macroeconomic indicators on BSE Sensex.  Results suggest a model where FDI significantly  influences the fluctuations in the stock market  in India.
Keywords: BSE Sensex; Stock Market; FDI; Stepwise Regression; India